2001
DOI: 10.1590/s1516-89132001000400002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterisation of a Reserve Protein from the Seeds of Cereus jamacaru (Cactaceae)

Abstract: We describe here the isolation and characterisation of a major reserve protein from the seeds of Cereus jamacaru. (Cactaceae). This protein has a molecular mass of 5319 kDa and was isolated by a combination of gel filtration chromatography and reverse phase HPLC. The amino acid composition of the protein was determined and it wasshown to have similarities with the amino acid composition of several proteins from the 2S albumin storage protein family. The usefulness of this protein as a molecular marker in the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Ep‐AMP1 is the first ICK peptide reported from the Cactaceae family. Indeed, few peptides have previously been described from this plant family: a methionine‐rich polypeptide from seeds of Cereus jamacaru ,30 an arginine‐rich polypeptide (48 residues, unsequenced) from Opuntia ficus‐indica 31 and a trypsin inhibitory peptide (38 residues) from Opuntia streptacantha . Compared to other ICK peptides, Ep‐AMP1 has high structural similarity to spider toxins, and lacks the chitin‐binding properties of peptides with the same sequence pattern (i.e., plant C6‐type antimicrobial peptides).…”
Section: Discussionmentioning
confidence: 99%
“…Ep‐AMP1 is the first ICK peptide reported from the Cactaceae family. Indeed, few peptides have previously been described from this plant family: a methionine‐rich polypeptide from seeds of Cereus jamacaru ,30 an arginine‐rich polypeptide (48 residues, unsequenced) from Opuntia ficus‐indica 31 and a trypsin inhibitory peptide (38 residues) from Opuntia streptacantha . Compared to other ICK peptides, Ep‐AMP1 has high structural similarity to spider toxins, and lacks the chitin‐binding properties of peptides with the same sequence pattern (i.e., plant C6‐type antimicrobial peptides).…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal properties have been attributed to the mandacaru, for example, as infusion for treatment of various diseases, including renal, hepatic, respiratory, stomach, and sinus problems (Agra et al 2007;Albuquerque et al 2007;Saraiva et al 2015;Silva et al 2014). Other studies have reported the cytotoxic activity of an aqueous extract (non-protein) from the stem (Silva 2015); antibacterial activity of ethanolic extract from the stem (Davet et al 2009); as well as the purification and characterization of two proteins from C. jamacaru seeds (Aragão et al 2000;da Costa et al 2001).…”
Section: Popular Use and Possible Applicationmentioning
confidence: 99%
“…The seeds by weight and volume of molar solution were used by 1:4 ratios. Then this supernatant was subjected to 12000 rpm for 20 min at 4°C and again the supernatant was collected for further processing (Costa et al 2001).…”
Section: Extract Preparationmentioning
confidence: 99%